Boosting Pseudocapacitive Behavior of Supercapattery Electrodes by Incorporating a Schottky Junction for Ultrahigh Energy Density - Selvaraj Seenivasan; Kyu In Shim; Chaesung Lim; Thangavel Kavinkumar; Amarnath T. Sivagurunathan; Jeong Woo Han; Do-Heyoung Kim (Nano-Micro Letters, 2023)
Highlights Incorporation of Schottky Junction increases the pseudocapacitive mechanism at higher current rate. The pseudocapacitance behavior of the positive and negative electrodes is balanced to construct a solid-state supercapattery device. An energy density of 236.14 Wh kg−1 is achieved for solid-state supercapattery device.